ACADEMIC WRITING AT THE UNIVERSITY OF CHICAGO: TRANSNATIONAL PERSPECTIVE - Tatyana D. Venediktova (Moscow Polytechnic University, 2022)
The author refers to teaching academic writing to PhD students at the University of Chicago, USA. The experience is regarded from the point of view of the 'local', nationally accepted attitudes and requirements, and the possibilities of applying these attitudes and requirements to the Russian higher education, which could help internationalize the learning environment in this country.